Encapsulation of Clitoria Ternatea/β Cyclodextrin - 'Izzati Nada 'Inani Binti Ibrahim; Saliza Binti Asman (Enhanced Knowledge in Sciences and Technology, 2023)
This research is to study the encapsulation of Clitoria ternatea and β-cyclodextrin. Clitoria ternatea, also known as butterfly pea, is an Asian plant known for its bright blue flowers. It has a high antioxidant content and is frequently used as a herbal tea and natural dye. β-cyclodextrins are cyclic molecules with a hydrophilic outer side and a hydrophobic cavity in the centre. Cyclodextrin can modify the physical and chemical properties of these molecules by incorporating the molecules into their cavities and forming inclusion complexes. The bioactive compounds in these C. ternatea flowers, on the other hand, are extremely sensitive to environmental changes. They do, however, require proper environmental protection to avoid damage to their structural integrity and bioactivity. Therefore, encapsulating Clitoria ternatea with β-cyclodextrin could help in create barriers between the environment and sensitive bioactive components. Based on the findings done in this research, the results shows that β-cyclodextrin increase the total flavonoid content in Clitoria ternatea and shows high antioxidant activity with high percentage of encapsulation efficiency of 70.87 ± 13.67 %. Furthermore, the encapsulation of Clitoria ternatea/β-cyclodextrin exhibit higher pH reading and moiture content of 5.61 ± 0.01 and 14.16 ± 0.28 % respectively than Clitoria ternatea.